Role of miR-211 in Neuronal Differentiation and Viability: Implications to Pathogenesis of Alzheimer’s Disease - Fan, Chunying; Wu, Qi; Ye, Xiaoyang; Luo, Hongxue; Yan, Dongdong; Xiong, Yi; Zhu, Haili; Diao, Yarui; Zhang, Wei; Wan, Jun (Frontiers in Aging Neuroscience, 2016)
Alzheimer’s disease (AD) is an age-related irreversible neurodegenerative disorder characterized by extracellular βAmyloid(Aβ) deposition, intracellular neurofibrillary tangles (NFT) and neuronal loss. The dysfunction of neurogenesis and increased degeneration of neurons contribute to the pathogenesis of AD. We now report that miR-211-5p, a small non-coding RNA, can impair neurite differentiation by directly targeting NUAK1, decrease neuronal viability and accelerate the progression of Aβ-induced pathologies. In this study, we observed that during embryonic development, the expression levels of miR-211-5p were down-regulated in the normal cerebral cortexes of mice. However, in APPswe/PS1delatE9 double transgenic adult mice, it was up-regulated from 9 months of age compared to that of the age-matched wild type (WT) mice. Studies in primary cortical neuron cultures demonstrated that miR-211-5p can inhibit neurite growth and branching via NUAK1 repression and decrease mature neuron viability. The impairments were more obvious under the action of Aβ. Our data showed that miR-211-5p could inhibit cortical neuron differentiation and survival, which may contribute to the synaptic failure, neuronal loss and cognitive dysfunction in AD.